2000
DOI: 10.1038/sj.gt.3301102
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle dependence of gene transfer by lipoplex, polyplex and recombinant adenovirus

Abstract: The aim of this study was to investigate the influence of cell cycle on transfection efficiency. Counterflow centrifugal elutriation was used which avoids possible side-effects from chemical treatment of cells. With this method, cell populations were fractionated by means of size and density, and fractions corresponding to discrete cell cycle phase-specific populations were transfected with various nonviral methods (Lipofectamine, TfpLys and TfPEI), adenovirus-enhanced transferrinfection (AVET system) and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
324
4
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(355 citation statements)
references
References 30 publications
25
324
4
2
Order By: Relevance
“…24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine. 28 The effect of photochemical treatment on EGFP expression in cells illuminated in different cell cycle phases was compared.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 99%
“…24,25 However, in spite of significant increase, they were not able to transfect the entire population of cells compared to the results obtained for photochemically enhanced adenovirus-mediated gene delivery. 26 By relying on the idea that the effectiveness of nonviral transfection systems depends on the cell cycle status, 27 they investigated the role of the cell cycle status in photochemical transfection mediated by two types of synthetic transfection agents: a cationic polypeptide polylysine (polyfection) and a cationic lipid formulation N-(2-amino ethyl)-N,N-dimethyl-2,3-bis(tetradecyloxy)-1-propanaminium bromide/dioleoylphosphatidyl ethanol amine. 28 The effect of photochemical treatment on EGFP expression in cells illuminated in different cell cycle phases was compared.…”
Section: Intelligent Polymeric Vectors In Gene Therapymentioning
confidence: 99%
“…During cell division, the nuclear membrane is temporarily disassembled, leading to the 'mitotic window of opportunity' in which the probability of pDNA to reach the nuclear interior of the newly formed daughter cells apparently increases significantly [7,8]. In a recent review, we proposed several strategies to enhance pDNA delivery during mitosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…As most target tissues are nondividing in vivo, the nuclear membrane is a major obstacle to gene transfer and must be circumvented to improve expression from nonviral vectors. [3][4][5][6][7][8] Our laboratory has begun to design plasmid vectors that achieve efficient gene expression by targeting constructs to the nuclear compartment of specific cell types. [9][10][11][12][13] Initially, we demonstrated that inclusion of as little as 72 bp of the simian virus 40 (SV40) promoter/ enhancer in plasmid vectors facilitates nuclear import in all cell types tested.…”
Section: Introductionmentioning
confidence: 99%